2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591232
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal weight variation patterns in seven countries located in northern and southern hemispheres

Abstract: The digital revolution of information and technology in late 20th century has led to emergence of devices that help people monitor their weight in a long-term manner. Investigation of population-level variations of body mass using smart connected weight scales enabled the health coaches acquire deeper insights about the models of people's behavior as a function of time. Typically, body mass varies when the seasons change. That is, during the warmer seasons people's body mass tend to decrease while in colder se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…This process refers specifically to the process of removing the overall trajectory of the time series thus centering the body weight and leaving the variability. Detrending of body weight data was conducted to account for the potentially confounding effect of weight change on patterns of variability as suggested previously [11,15]. For weekly and Christmas analyses, the body weight data was detrended by fitting a LOESS (locally estimated scatterplot smoothing) regression (S2A Fig) to each participant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process refers specifically to the process of removing the overall trajectory of the time series thus centering the body weight and leaving the variability. Detrending of body weight data was conducted to account for the potentially confounding effect of weight change on patterns of variability as suggested previously [11,15]. For weekly and Christmas analyses, the body weight data was detrended by fitting a LOESS (locally estimated scatterplot smoothing) regression (S2A Fig) to each participant.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, holiday (typically Christmas) weight gain has been well documented with increases in weight in the region of 0.4-1kg being reported consistently across the UK, Europe, North America and Japan [13]. Seasonal fluctuations across the year are often less pronounced and more inconsistent, though may be characterized by a decrease in weight during the summer and an increase in the winter [14][15][16] which has been shown in both Northern and Southern hemispheres [15]. Indeed, it is possible that in each of these cases, short-term increases in weight partially contribute to long-term weight gain.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Seasonal variations in body weight have been consistently reported. In European and North American countries, body mass index (BMI) is on average higher in the winter than in the summer (Mehrang, Helander, Chieh, & Korhonen, ). This pattern has been found both in the general population (Visscher & Seidell, ) and in overweight adults participating in a behavioral weight loss intervention (Fahey, Klesges, Kocak, Talcott, & Krukowski, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Although there would seem to be an increase in EI with CE in humans, the data are scarce and inconclusive at best. Furthermore, studies pertaining to seasonal variations in environmental temperature have shown that body weight increases in the winter, although this is associated with increased EI and decreased physical activity. The purpose of this review is to provide a comprehensive overview of available literature on the effects of CE on EI and appetite from both animal and human studies, as well as compensation in response to chronic CE.…”
Section: Introductionmentioning
confidence: 99%